The Social Construction of the Technological Future: Suyusama – a Case Study - Moreno, Juan Carlos (2010)
This article presents the theoretical and methodological contributions of research developed in the south of Colombia –the Andean region of Nariño– within the framework of a social development project entitled “Suyusama Program.” This research made possible the identification and prioritizing of technological challenges in the development plans of 25 municipal communities and oriented their implementation. The research contributes a group of categories, variables, and methodological processes for the social construction of the technological future through community participation. These contributions face a number of limitations regarding what has been called social technology and regarding the social construction of technology. In addition, there emerges a way to make concrete and operative that proposed by the concept of social-technical appropriateness.